Predictors of Nursing Board Examination Performance - Navarro, Remedios T.; Vitamog, Aurelia T.; Tierra, Rizza Joy C.; Gonzalez, Donna Marie J. (JPAIR Multidisciplinary Research, 2011)
This study determines if the UNP College Admission Test (UNP CAT), Nursing Aplitude Test (NAT) and academic performance are significant predictors of the Nursing Board Examination Performance of the graduates of the University of Northern Philippines for the period 2006-2009. The descriptive-correlational method of research was employed with documentary analysis as primary tool for data gathering. The respondents consisted of the 750 Bachelor of Science in nursing graduates, who were first takers of the Nursing Board Examination. Data were analyzed through frequency, percentage and multiple regression analysis. Majority of the Nursing graduates performed at a good level in the UNP-CAT, and at a very good level in their academics. Most performed at an average passed level in the NAT, and majority, at a fair level, in the Nursing Board Examination. The UNP-CAT, NAT and academic performance, taken singly and as a whole are significant predictors of performance in the Nursing Board Examination. Students who perform better in the UNP-CAT, NAT, and in their academics tend to perform better in the Nursing Board Examination. Academic performance as the best predictor underscores the importance of the kind of education and training the university provides to its student try.